The Effect of Service Quality on Customer Satisfaction in PT Orange Indonesia Mandiri - Christine, Derika; Nugroho, Ngajudin; Hutabarat, Fauzi Akbar Maulana (ADPEBI, 2022)
This study aims to determine the effect of service quality on customer satisfaction at PT. Orange Indonesia Mandiri. The samples used in this study were 80 customers who had made transactions at PT. Orange Indonesia Mandiri. The method of data collection in this study was done by distributing a closed questionnaire with a Likert scale. Based on the results of the correlation coefficient, service quality (X) and customer satisfaction (Y) have a strong relationship with a value of 0.674. The results of the coefficient of determination test show that service quality has an effect of 45.4% and the rest is influenced by other factors not tested in this study. Meanwhile, from the results of the hypothesis test z-count > z-table (5.97 <1.96), it means that service quality has a significant effect on customer satisfaction.